Hubungan Faktor Resiko Pada Ibu Hamil Trimester III Dengan Kadar Gula Darah - Endriyani Martina Yunus; Susan Delilah; Marlina Santi (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2021)
It is estimated that the incidence of diabetes in pregnancy is 0.7%, but it is often difficult to find due to the low case detection ability (Nurrahmani, 2012). This study aims to determine the relationship between risk factors in trimester III pregnant women with blood sugar levels and weight of newborns in the work area of ​​Tempilang Public Health Center in 2019. This type of research is cross sectional, using primary data. The results of this study there are 5 respondents (10.6%) pregnant women with age at risk (<20-> 35 years), 5 respondents (10.6%) pregnant women who have a genetic history of diabetes, 28 respondents (59.6%) overweight pregnant women, 1 respondent (2.1%) pregnant women with a history of giving birth to a big baby, 1 respondent (2.1%) pregnant women with blood sugar levels> 140 mg / dl 2 hours after eating. Based on the results of bivariate analysis with p-value> 0.05, which shows that there is no relationship between maternal age, genetic, body weight, and history of macrosomia with blood sugar levels of third trimester pregnant women in the Work Area of ​​Puskesmas Tempilang in 2019. For this reason, every pregnant woman who checks her pregnancy needs to be examined blood glucose levels in pregnant women since the second trimester as an early detection of gestational diabetes and provide knowledge to pregnant women about the dangers of diabetes in pregnancy.